2011
DOI: 10.1103/physrevlett.106.120403
|View full text |Cite
|
Sign up to set email alerts
|

Faithful Entanglement Swapping Based on Sum-Frequency Generation

Abstract: We show that an entanglement swapping operation performed with spontaneous parametric down-conversion can be made faithful without postselection using sum-frequency generation. This invites us to revisit the sum-frequency process and from a proof-of-principle experiment, we demonstrate that it provides a realistic solution for nonlinear optics at the single-photon level. This opens the way to attractive alternatives to six-photon protocols based on linear optics used, e.g., for the heralded creation of maximal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 26 publications
2
78
1
Order By: Relevance
“…The telecom photons generated by the SPDC source are combined with the coherent state pulses from the DFG source using a dense wavelength division multiplexer (DWDM). We verified the single-photon nature of the SPDC source by measuring the conditional second-order correlation function of the telecom photon after the DWDM to be g (2) (0) ¼ 0.03.…”
Section: Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…The telecom photons generated by the SPDC source are combined with the coherent state pulses from the DFG source using a dense wavelength division multiplexer (DWDM). We verified the single-photon nature of the SPDC source by measuring the conditional second-order correlation function of the telecom photon after the DWDM to be g (2) (0) ¼ 0.03.…”
Section: Sourcesmentioning
confidence: 99%
“…Realizing such an interaction is not only fundamentally fascinating but holds great potential for emerging technologies. It has recently been shown that even weak optical nonlinearities between single photons can be used to perform important quantum communication tasks more efficiently than methods based on linear optics 2 , which have fundamental limitations 3 . Nonlinear optical effects at single-photon levels in atomic media have been studied 4,5 and demonstrated [6][7][8][9] , but these are neither flexible nor compatible with quantum communication, as they impose restrictions on photons' wavelengths and bandwidths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 to be used for device-independent quantum key distribution based on the CHSH inequality, as the secret key fraction goes to zero for S ∼ 2.43 under the assumption of collective attacks [7]. Note that a higher violation can be obtained through amplification [8] or non-linear filtering [9] at the price of increasing complexity. An alternative solution is based on conditioning, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our method employs sum-frequency generation (SFG) [43][44][45][46] together with linear optical components and classical photodetectors. SFG has already exhibited its usefulness in quantum information [47][48][49][50][51][52] and device-independent QKD [53] at the single-photon level. Here we use it in the conventional non-linear optics paradigm with strong coherent light.…”
Section: Either a Linear (H [Horizontal] Or V [Vertical]) Or A Circulmentioning
confidence: 99%